Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{x}{3}=\frac{y}{4}\)
=> \(\frac{x^2}{3^2}=\frac{y^2}{4^2}\)
\(\frac{x^2}{9}=\frac{y^2}{16}=\frac{2.x^2+y^2}{2.9+16}=\frac{136}{34}=4\)
=> \(\frac{x^2}{9}=4\) => x2 = 4.9 = 36 => x = 6 hoặc -6
Với x = 6 thì y = 4.6/3 = 8
Với x = -6 thì y = 4.(-6)/3 = -8
ĐS: x = 6,y = 8;
x = -6, y = -8
\(\dfrac{1}{2x}+\dfrac{1}{2y}+\dfrac{1}{xy}=\dfrac{1}{2}\)
\(\dfrac{y}{2xy}+\dfrac{x}{2xy}+\dfrac{2}{2xy}=\dfrac{xy}{2xy}\)
=> x + y + 2 = xy
x + y - xy = -2
x.( 1 - y ) + y = -2
x.( 1 - y ) - ( 1 - y ) = -2 - 1
( 1 - y ).( x - 1 ) = -3
- ( y - 1 ).( x - 1) = -3
=> ( y - 1 ).( x - 1 ) = 3
=> ( y - 1 ) ; ( x - 1 ) \(\in\) Ư( 3 ) = { 1; -1; 3; -3 }
Ta có bảng sau
y - 1 | 1 | -1 | 3 | -3 |
y | 2 | 0 | 4 | -2 |
x - 1 | 3 | -3 | 1 | -1 |
x | 4 | -2 | 2 | 0 |
Vậy ( x ; y ) \(\in\) { ( 4 ; 2 ); ( -2 ; 0 ); ( 2; 4 ); ( 0; -2 ) }
\(2^n-1⋮7\Rightarrow2^n-1=7k\left(k\in N\right)\)
\(\Rightarrow2^n=7k+1\)
Vì \(7k+1\) luôn lẻ với mọi k Để \(2^n=7k+1\Leftrightarrow n=0\)
Với \(n=0\) thì \(2^0-1=1-1=0⋮7\)
Vậy \(n=0\)